Project-Time Resource Distribution of Socio-Economic Systems - Pereverzieva Anna, Volkov Volodymyr (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The dynamics of change in the economic environment, uncertainty and risk significantly affect the development of socio-economic systems, which manifests itself in the need to allocate scarce resources to achieve the maximum level of projects` implementation.The method of resource distribution in complex socio-economic systems aimed at their optimum utilization is proposed in the study. The result of the division is the ability to make rational decisions on optimizing, distributing and managing material, financial and other resources, reducing the risk of negative consequences for essential services` provision and overall processes` functioning, their management.Our study allowed to prove that building of the optimal resource distribution model should rationally apply a geometric figure – a circle for determining the optimal resource costs according to their redistribution between projects or stages of projects taking into account the time criterion.After all, the circle has the smallest area of surface of the equivalent geometric figures. Applying this property to resource distribution as the trajectory for use of resource makes it possible to minimize resource consumption with time.The proposed method of distribution is practically implemented in the activities of a socio-economic system – a united territorial community to automate the process of allocation of the budget financial resources` distribution. This made it possible to achieve optimization of instantly important processes taking time criterion into account.The proposed method belongs to the complex processes` resource management and can be used to optimize the resource provision of the process in general and its subsystems in real time. It implies obtaining qualitative and quantitative process` estimations and increase the optimization level of resource costs.